The repetitive component of the A genome of peanut (Arachis hypogaea) and its role in remodelling intergenic sequence space since its evolutionary divergence from the B genome - Bertioli, David J. (2013)
Fil: Bertioli, David J. University of Brasilia. Department of Genetics, Campus Universitário, Brasília DF; Brazil.